2011
DOI: 10.1007/s10029-011-0898-6
|View full text |Cite
|
Sign up to set email alerts
|

Does expanded polytetrafluoroethylene mesh really shrink after laparoscopic ventral hernia repair?

Abstract: Our results are markedly different from animal studies and show that ePTFE has minimal shrinkage after LIVH repair. The use of transfascial sutures in addition to tack fixation may have an implication on the mesh contraction rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
1
9
2
Order By: Relevance
“…Schoenmaeckers et al [21] reported that shrinkage of ePTFE in 656 patients who underwent laparoscopic hernia repair was only 7.5 % when measured by CT. This was recently confirmed by Carter et al [22] who reported a mean shrinkage rate of 6.7 %, confirming that ePTFE has minimal contraction in the human clinical situation.…”
Section: Discussionsupporting
confidence: 70%
“…Schoenmaeckers et al [21] reported that shrinkage of ePTFE in 656 patients who underwent laparoscopic hernia repair was only 7.5 % when measured by CT. This was recently confirmed by Carter et al [22] who reported a mean shrinkage rate of 6.7 %, confirming that ePTFE has minimal contraction in the human clinical situation.…”
Section: Discussionsupporting
confidence: 70%
“…Several authors have reported ePTFE mesh contraction rates of approximately 40% in experimental studies performed in animals . In contrast, postoperative CT findings in humans have shown minimal contraction of ePTFE mesh compared with animal models . In our LVHR cases, the contraction rate of ePTFE mesh was 10.6%, a little larger than the rates previously reported in human models.…”
Section: Discussioncontrasting
confidence: 71%
“…Two retrospective studies reported 6.7 and 7 % shrinkage of ePTFE mesh measured by computed tomography [113,114]. These results were markedly lower than those determined in animal studies.…”
Section: Safetycontrasting
confidence: 43%